Interventional research to tackle antimicrobial resistance in Low Middle Income Countries in the era of the COVID-19 pandemic: lessons in resilience from an international consortium. (April 2022) - Birgand, Gabriel; Charani, Esmita; Ahmad, Raheelah; Bonaconsa, Candice; Mbamalu, Oluchi; Nampoothiri, Vrinda; Surendran, Surya; Weiser, Tom G.; Holmes, Alison; Mendelson, Marc; Singh, Sanjeev; ,
Highlights: The COVID-19 pandemic has helped challenge the usual way of doing research. A prolonged on-site presence at the early stage of projects is critical. Research should rely on a capacity-building strategy to provide local skills. Funding should be proportionate to the cost of resources and gaps in each low middle income countries setting. Abstract: This article summarizes the consequences of the COVID-19 pandemic, on an international project to tackle antimicrobial resistance (AMR). The research leadership and process, the access to data, and stakeholders were deeply disrupted by the national and international response to the pandemic, including the interruption of healthcare delivery, lockdowns, and quarantines. The key principles to deliver the research through the pandemic were mainly the high degree of interdisciplinary engagement with integrated teams, and equitable partnership across sites with capacity building and leadership training. The level of preexisting collaboration and partnership were also keys to sustaining connections and involvements throughout the pandemic. The pandemic offered opportunities for realigning research priorities. Flexibility in funding timelines and projects inputs are required to accommodate variance introduced by external factors. The current models for research collaboration and funding need to be critically evaluated and redesigned to retain the innovation that was shown to be successful through this pandemic.